Composição fitoquímica, avaliação do perfil toxicológico e atividade protetora frente a intoxicação por mercúrio das folhas de Dolichandra unguis-cati L. - Brondani, Juliana Calil (2016)
Dolichandra unguis-cati L., popularly known as unha de gato, is a native plant of Brazilian flora, belonging to the Bignoniaceae family and widely used for therapeutic and ornamental purposes. It has been traditionally used in popular medicine mainly due to its anti-inflammatory, anti-tumor, anti-malarial and febrifuge activities. However, studies on the biological properties and safety in the use of this plant species are still lacking in the literature. Thus, the objective of this work was to investigate the phytochemical composition, toxicological profile and protective activity of the hydroethanolic extract of Dolichandra unguis-cati leaves (CELD) against the mercurial intoxication of Wistar rats. The phytochemical composition was established by spectrophotometric methods and UHPLC/MS. The toxicological analysis initially comprised in vitro studies of cytotoxicity (cell viability), genotoxicity (DNA comet) and mutagenicity (micronuclei). Followed by the ex vivo toxicities, acute (OECD 423) and subacute (OECD 407), complemented by the in vitro lethality test using Artemia salina. The protective action of the extract, against mercury chloride intoxication (HgCl2) of rats, was assessed through biochemical and hematological parameters and by the determination of the antioxidant capacity of CELD, by DPPH and β-carotene. As a result, 12 chemical constituents of the extract were identified and quantified, which may be related to the potential antioxidant activity verified by DPPH (IC50 29.18 μg/mL) and β-carotene (39% inhibition of oxidation) tests. In the concentrations of 10 and 100 μg/mL, CELD was able to decrease the cellular viability of human leukocytes in a dose-dependent manner, suggesting a possible anti-tumor action. In addition, none of the concentrations tested (1, 10 and 100 μg/mL) resulted in genotoxicity and mutagenicity. In the acute toxicity study, we observed that the treatment with CELD 2000 mg/kg did not cause mortality or changes in body weight and behavior of rats, classifying the species as category 5 of OECD 423, with a LD50 estimated between 2000-5000 mg/kg, complemented by the LD50 of 3539.54 μg/mL obtained in the test with Artemia salina. The subacute administration of CELD, at doses of 100, 200 and 400 mg/kg for 28 days, also did not present death of animals, changes in behavior and body weight. In both ex vivo studies, a reduction in AST and ALT dosages was observed, indicating a possible hepatoprotective effect. The subacute treatment was also effective in reducing total cholesterol in all concentrations tested, suggesting a potential applicability of CELD in the dyslipidemia treatment. Ultimaly, CELD 400 mg/kg attenuated the toxic effects resulting from HgCl2 intoxication through restoration of the oxidative balance, decrease in AST, ALT, BUN and CRE dosages, increase in WBC levels and reversal of the inversion between lymphocytes and neutrophils. In this way, CELD demonstrated to present low toxicity and potential biological activities that justify its uses as a medicinal plant.